Military history museums of Ukraine: historical and statistical aspects - Mashtalir, V.V. (Питання історії науки і техніки, 2014)
In the article the results of military-historical museums Ukraine through characterization of their foundations and excursion work. У статті висвітлено результати діяльності військово-історичних музеїв України через характеристику їх фондів та екскурсійну роботу. В статье освещены результаты деятельности военно-исторических музеев Украины через характеристику их фондов та экскурсионную работу.